Signaling Danger: Toll-Like Receptors and Their Potential Roles in Diseases - Hadi, Najah R.; Shaker, Saad Rasool; Alharis, Nada R (Important Aspects of Toll-like Receptors: Signaling Pathways in Diseases, 2021)
Toll-like receptors (TLR) are an emerging family of receptors that recognize pathogen-associated molecular patterns and promote the activation of leukocytes and intrinsic renal cells. Ligands of the TLR include exogenous microbial components such as LPS (TLR4), lipoproteins and peptidoglycans (TLR1, -2, -6), viral RNA (TLR3), bacterial and viral unmethylated cytosin-guanosin dinucleotide (CpG)-DNA (TLR9), and endogenous molecules including heat-shock proteins and extracellular matrix molecules. Upon stimulation, TLR induce expression of inflammatory cytokines or costimulatory molecules via the MyD88-dependent and MyD88-independent signaling pathways shared with the interleukin-1 receptors. TLR are differentially expressed on leukocyte subsets and non-immune cells and appear to regulate important aspects of innate and adaptive immune responses. Tubular epithelial cells are among the non-immune cells that express TLR1, -2, -3, -4, and -6, suggesting that these TLR might contribute to the activation of immune responses in tubulointerstitial injury (e.g., bacterial pyelonephritis, sepsis, and transplant nephropathy). The role of Toll-like receptors as a primary part of our microbe defense system has been shown in several studies, but their possible function as mediators in allergy and asthma remains to be established. An important contributor to microglial activation is toll-like receptor 4, a pathogen-associated molecular pattern receptor known to initiate an inflammatory cascade in response to various CNS stimuli.